Impact f pre- and post-procedural renal dysfunction on long-term outcomes in patients undergoing MitraClip implantation: A retrospective analysis from two German high-volume centres. (1st February 2020) - Kalbacher, Daniel; Daubmann, Anne; Tigges, Eike; Hünlich, Marc; Wiese, Sabrina; Conradi, Lenard; Schirmer, Johannes; Beuthner, Bo Eric; Reichenspurner, Hermann; Wegscheider, Karl; Danner, Bernhard C.; Tichelbäcker, Tobias; et al.
Highlights: Acute kidney injury after MitraClip implantation increases mortality rates. AKI deteriorates long-term prognosis significantly more than CKD. Suffering from CKD significantly increases the likelihood of an AKI-episode. Renal function should be monitored after MitraClip implantation.